Through the End of the Cretaceous in the Type Locality of the Hell Creek Formation in Montana and Adjacent Areas 2014
DOI: 10.1130/2014.2503(07)
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary test of the press-pulse extinction hypothesis: Palynological indicators of vegetation change preceding the Cretaceous-Paleogene boundary, McCone County, Montana, USA

Abstract: Many workers consider the Cretaceous-Paleogene extinction the archetypal catastrophic pulse event caused solely by the Chicxulub bolide impact. However, based on a global scale analysis of marine animals, the Cretaceous-Paleogene boundary is a candidate for an extinction enhanced by the coincidence of press and pulse disturbances. We make a preliminary test of key predictions of the press-pulse hypothesis using palynological data. We document a local palynological extinction of 21% at the Cretaceous-Paleogene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…It is therefore impossible at this point to separate the influences of the meteorite and the additional volcanism in driving the second phase of extinction or in causing the second warming pulse. Nevertheless, the full magnitude of the end-Cretaceous extinction at this site can be attributed to the combined influence of Deccan Traps volcanism and the meteorite impact event, previously described as a press-pulse extinction mechanism 48 49 . Importantly, the pre-KPB warming, which itself correlated with significant extinction, may have increased ecosystem stress, making the ecosystem more vulnerable to collapse when the meteorite hit.…”
Section: Discussionmentioning
confidence: 79%
“…It is therefore impossible at this point to separate the influences of the meteorite and the additional volcanism in driving the second phase of extinction or in causing the second warming pulse. Nevertheless, the full magnitude of the end-Cretaceous extinction at this site can be attributed to the combined influence of Deccan Traps volcanism and the meteorite impact event, previously described as a press-pulse extinction mechanism 48 49 . Importantly, the pre-KPB warming, which itself correlated with significant extinction, may have increased ecosystem stress, making the ecosystem more vulnerable to collapse when the meteorite hit.…”
Section: Discussionmentioning
confidence: 79%
“…The color change between gray and yellow sediments occurs below the MCZ coal and is roughly coincident with a ~10-cm-thick carbonaceous shale layer. This carbonaceous shale layer is also coincident with a negative carbon isotope excursion (measured near the Z-Line locality at McGuire Creek), which Arens et al (2014) claystone nor the Nirvana bentonite layer, which was derived from a tephra unique to the IrZ coal found in Garfield County (Ickert et al (2015), is readily apparent. It is therefore possible that the carbonaceous shale layer may be roughly correlative to the IrZ coal.…”
Section: Geologic Settingmentioning
confidence: 74%
“…It grades laterally into coal, and ~4 cm from the top of the layer is a 1-2-cm-thick fine-grained pink (Munsell color 5 R 6/2) siltstone. This carbonaceous shale layer can be visually traced to the carbonaceous shale measured by Arens et al (2014) where the negative carbon isotope excursion was identified. A 1-2-cm-thick, lightgray to pink claystone forms the lower bound to the carbonaceous shale.…”
Section: Mammalian Fossil Localities: Geological Descriptionsmentioning
confidence: 99%
“…Similarly, Arens et al. () provided evidence on the relative abundance of angiosperms rather than gymnosperms at the Cretaceous–Paleogene boundary in the Hell Creek Formation, even if angiosperms were characterized by a species decline during the Late Maastrichtian. Recent works (Lupia et al.…”
Section: Discussionmentioning
confidence: 95%